1991
DOI: 10.1073/pnas.88.22.10004
|View full text |Cite
|
Sign up to set email alerts
|

The nonphosphorylated form of RNA polymerase II preferentially associates with the preinitiation complex.

Abstract: The two forms of RNA polymerase H that exist in vivo, phosphorylated (HO) and nonphosphorylated (HA), were purified to apparent homogeneity from HeLa cells. The nonphosphorylated form preferentially binds to the preinitiation complex. RNA polymerase H in the complex was converted by a cellular protein kinase to the phosphorylated form.Purified RNA polymerase II cannot accurately initiate transcription from class II promoters in vitro unless it is supplemented with general transcription initiation factors (1-3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
230
0

Year Published

1995
1995
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(248 citation statements)
references
References 35 publications
16
230
0
Order By: Relevance
“…Phosphorylation of the CTD allows the removal of TFIIB, TFIIE and TFIIH (promoter clearance) [30,48,49], which in turn permits RNA pol IIo (phosphorylated form of RNA pol II) [49,50] to commence elongation [42]. Once elongation has been terminated, RNA pol IIo detaches from the DNA and, before it can re-enter initiation, the CTD must be dephosphorylated [47,51]. Assembly of the GTFs has been extensively reviewed in [30,49,52].…”
Section: Figure 1 Gtf Assembly At a Typical Eukaryotic Promotermentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of the CTD allows the removal of TFIIB, TFIIE and TFIIH (promoter clearance) [30,48,49], which in turn permits RNA pol IIo (phosphorylated form of RNA pol II) [49,50] to commence elongation [42]. Once elongation has been terminated, RNA pol IIo detaches from the DNA and, before it can re-enter initiation, the CTD must be dephosphorylated [47,51]. Assembly of the GTFs has been extensively reviewed in [30,49,52].…”
Section: Figure 1 Gtf Assembly At a Typical Eukaryotic Promotermentioning
confidence: 99%
“…TFIIH has a kinase activity which can phosphorylate the CTD [57], and it appears that mediator confers a 30-50-fold stimulation of this TFIIH-dependent phosphorylation [44,59]. Finally, RNA pol IIo dephosphorylation has been attributed to the holoenzyme complex [47,51,60].…”
Section: Non-structural Functions Of the Gtfsmentioning
confidence: 99%
“…These results indicate the special roles of the CTD in transcription and, ultimately, in ensuring cell viability. In fact, it has been reported that PolII possessing the hyperphosphorylated CTD of the largest subunit (IIo form) does not participate in the transcription PIC (Lu et al 1991), while actively transcribing PolII contains the IIo form of the largest subunit (Weeks et al 1993;O'Brien et al 1994). Recently, it was reported that the phosphorylated CTD has a role in recruiting the mRNA capping enzyme to the nascent transcript and that mRNA capping occurs soon after promoter clearance (Coppola et al 1983;Cho et al 1997;McCracken et al 1997a,b;Yue et al 1997).…”
Section: Tfiih Is the Only Kinase Active In The Transcription Preinitmentioning
confidence: 99%
“…The CTD has been shown to interact with various factors which form the preinitiation multi-polypeptide complex, including the TATAbinding protein (TBP) and the PolII/SRB (suppressor of RNA polymerase B)/Med (mediator found as a component of yeast holoenzyme) complex (Usheva et al 1992; Thompson et al 1993;Myers et al 1998). The unphosphorylated form of PolII (Pol IIa) is preferentially recruited into the PIC reconstituted from puri®ed general transcription factors (Lu et al 1991). CTD phosphorylation may initially occur between transcription initiation and the transition from initiation to elongation, converting PolII to the phosphorylated form (Pol IIo) (O'Brien et al 1994;Svejstrup et al 1996;Ohkuma 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike RNAPs I and III, the largest subunit of RNAP II has a characteristic carboxyl-terminal repeat domain [17], which is the site of multiple phosphorylation/ dephosphorylation reactions which control intraconversion of the two forms [18,19]. The largest subunit of RNAP IIO (designated IIo) is conformationally distinct from that of RNAP IIA (subunit IIa) [20], and the two forms of the enzyme are active at different stages of the transcription process, sometimes in a site-specific manner [18,[21][22][23][24]. It is therefore possible that autoantibodies could recognize either one or both types of RNAP II.…”
Section: Introductionmentioning
confidence: 99%